2013
DOI: 10.1242/jeb.083576
|View full text |Cite
|
Sign up to set email alerts
|

Economic design in a long-distance migrating molluscivore: how fast-fuelling red knots in Bohai Bay, China, get away with small gizzards

Abstract: SUMMARYWe carried out an observational and experimental study to decipher how resource characteristics, in interaction with the predator's phenotype, constrain a fitness-determining performance measure, i.e. refuelling in a migrant bird. Two subspecies of red knot (Calidris canutus rogersi and C. c. piersmai) use northern Bohai Bay, Yellow Sea, China, for the final prebreeding stopover, during their 10,000-15,000km long migrations between wintering and breeding areas. Here, they feed on small bivalves, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 52 publications
4
73
0
Order By: Relevance
“…In sum, adjustments in gut size of a variety of vertebrates require at least a few days, and perhaps as much as one week, depending on body size and type of digestive change [19,42,54]. For actively migrating birds that fast while flying and must stop to feed and refuel, this pace of digestive change may often be too slow, and so digestive constraints may directly retard the pace of migration [42,77,78].…”
Section: Discussionmentioning
confidence: 99%
“…In sum, adjustments in gut size of a variety of vertebrates require at least a few days, and perhaps as much as one week, depending on body size and type of digestive change [19,42,54]. For actively migrating birds that fast while flying and must stop to feed and refuel, this pace of digestive change may often be too slow, and so digestive constraints may directly retard the pace of migration [42,77,78].…”
Section: Discussionmentioning
confidence: 99%
“…2). We back-transformed these estimates to yield outputs in mg. To link intake to metabolizable energy, we converted estimates of shell ballast intake into their energetic equivalent (kJ g −1 shell ballast) assuming an energy density of 22 kJ g −1 AFDM Macoma flesh (van Gils et al, 2005b;Zwarts and Wanink, 1993) and an assimilation efficiency of 0.8 (Yang et al, 2013).…”
Section: Experimental Animals and Maintenancementioning
confidence: 99%
“…During the nonbreeding season, shorebirds experience high energetic demands (Kersten and Piersma, 1987;Wiersma and Piersma, 1994), a natural history trait that also makes shorebirds ideal study subjects of the interplay between an organism's foraging ecology and its energetic requirements (Kvist and Lindström, 2003;van Gils et al, 2005a;Yang et al, 2013). Previous studies of intake rates in shorebirds have demonstrated that they rapidly increase with prey density, but quickly reach an asymptote beyond which intake rates stabilize.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shell thickness and resistance to crushing vary among species of molluscs (Cabral & Jorge 2007) and even among seasons (Nagarajan et al 2006). As Dosinia and especially Loripes are thin-shelled prey that can be crushed easily (Yang et al 2013), we were concerned that a large fraction of shell mass in droppings is lost in the sieving process given the fixed mesh of 300-μm used by . We expect this fraction to be larger than the fractions found by for more thick-shelled prey from the Wadden Sea.…”
mentioning
confidence: 99%